Pengaruh Fraud Risk Assessment dan Independensi Terhadap Kemampuan Auditor Mendeteksi Kecurangan Dengan Skeptisme Profesional Sebagai Variabel Intervening (Studi Kasus Pada Kantor Perwakilan Badan Pengawasan Keuangan dan Pembangunan (BPKP) Provinsi Kalimantan Barat) - Putri, Atika Wulandari (JAAKFE UNTAN (Jurnal Audit dan Akuntansi Fakultas Ekonomi Universitas Tanjungpura), 2021)
The purpose of this study is to examine the effect of fraud risk assessment and independence on the auditor's ability to detect fraud with professional skepticism as an intervening variable. The data used in this study are primary data. The method of data collection is done by giving questions in the form of questionnaires to respondents. The population of this research is all auditors who work in the Representative Office of the Financial and Development Supervisory Agency (BPKP) of West Kalimantan Province. The selection of this sample uses a purposive sampling technique and the sample obtained is 35 auditors. The data analysis technique was performed using the Structural Equation Modeling (SEM) method with the Partial Least Square (PLS) approach using WarpPLS 6.0 software. The results showed that fraud risk assessment was positive and significant on the auditor's ability to detect fraud. Independence had a positive effect but was not significant on the auditor's ability to detect fraud. Professional skepticism becomes a partial mediating variable between the assessment of fraud risk of the auditor's ability to detect fraud and becomes a complete mediating variable between the independence of the auditor's ability to detect fraud.